2018
DOI: 10.1002/jez.b.22811
|View full text |Cite
|
Sign up to set email alerts
|

An alternative evolutionary pathway for the twin‐tail goldfish via szl gene mutation

Abstract: The twin‐tail of ornamental goldfish provides unique evolutionary evidence that the highly conserved midline localization of axial skeleton components can be changed by artificial selection. This morphological change is known to be caused by a nonsense mutation in one of the recently duplicated chordin genes, which are key players in dorsal–ventral (DV) patterning. Since all of the multiple twin‐tail ornamental goldfish strains share the same mutation, it is reasonable to presume that this mutation occurred on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
4
5
0
Order By: Relevance
“…We compared the amino acid sequences of candidate gene paralogs (Data S1P). We observed that the paralogs S and L show clearly higher identities (80%-92% amino acid identity) than those between paralogs a and b (44%-56% amino acid identity), reflecting the ancient history of Cs4R and Ts3R [11][12][13][14][15], consistent with previous studies [62][63][64][65]. We also compared the expression of these paralogs (Data S1O).…”
Section: Discussionsupporting
confidence: 85%
“…We compared the amino acid sequences of candidate gene paralogs (Data S1P). We observed that the paralogs S and L show clearly higher identities (80%-92% amino acid identity) than those between paralogs a and b (44%-56% amino acid identity), reflecting the ancient history of Cs4R and Ts3R [11][12][13][14][15], consistent with previous studies [62][63][64][65]. We also compared the expression of these paralogs (Data S1O).…”
Section: Discussionsupporting
confidence: 85%
“…In fact, this interpretation allows us to explain why the majority of our F2 backcross progenies consistently exhibited mutant phenotypes in dorsal, anal, and caudal fins (Supplementary Tables S1 , S2 ). Moreover, previous reports on szl -depleted goldfish are consistent with this interpretation 18 , 33 . Depletion of szl gene expression in goldfish embryos leads to the dorsal-finless phenotype, which is related to the chordin gene 33 .…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, previous reports on szl -depleted goldfish are consistent with this interpretation 18 , 33 . Depletion of szl gene expression in goldfish embryos leads to the dorsal-finless phenotype, which is related to the chordin gene 33 . Although the detailed molecular developmental mechanisms of the dorsal fin disappearance are still unknown, it is certain that the depletion of this gene disrupts dorsal–ventral patterning to generate the dorsal-finless phenotype in the goldfish 33 .…”
Section: Discussionsupporting
confidence: 75%
“…In fact, this interpretation allows us to explain why the majority of our F2 backcross progenies consistently exhibited mutant phenotypes in dorsal, anal, and caudal fins (Supplementary Table S1 and S2). Moreover, previous reports on szl-depleted goldfish are consistent with this interpretation 18,33 . Depletion of szl gene expression in goldfish embryos leads to the dorsal-finless phenotype, which is related to the chordin gene.…”
Section: Discussionsupporting
confidence: 73%
“…Depletion of szl gene expression in goldfish embryos leads to the dorsal-finless phenotype, which is related to the chordin gene. Importantly, the depletion of this gene disrupts dorsal-ventral patterning to generate the dorsal-finless phenotype in the goldfish 33 .…”
Section: Discussionmentioning
confidence: 99%